The Qur’anic account of Jews and Christians: expository analysis - Hashi, Abdurezak Abdulahi (Center for Promoting Ideas, 2012)
Jews and Christians are among well illustrated religious communities in the Qur’an. Various religious teachings and belief system of these two communities were elaborated in the Qur’an. They are known in the Qur’an as ahl al-kitÉb (the People of the Book), the title which demonstrates their lineage to Islam. This paper attempts to examine the status of the Jews and Christians in the Qur’an, and to present the Qur’anic response towards the teachings of these two particular religious faiths. Keywords: Jews, Christians, Qur’anic perspective, exposition and analysis